The rated sweetness of infant formulas and childhood anthropometric measures - Olson, Chelsea (My University, 2024)
Background: The U.S. Food and Drug Administration regulates infant formula to assure nutritional and safety standards are meet. However, the components of infant formula can vary markedly, and the carbohydrate content which may contain added sugars remains largely unregulated. While the components of infant formula are known to vary in sweetness intensity, limited knowledge exists regarding the relationship between the sweetness of infant formulas and childhood anthropometric measurements. Purpose: This study was conducted to evaluate the sweetness levels of infant formulas and explore the relationship between sweetness ratings and anthropometric measurements recorded during early childhood. Methods: A trained sensory panel (n = 15) was used to evaluate the sweetness intensity of six commonly used infant formulas. Each sample was tested by the full panel during three separate sessions (triplicate testing). The sweetness ratings were then combined with a dataset (n = 16,451) from a Southern California agency of the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). Infant formula sweetness ratings for the four formulas issued by the agency were dichotomized (score = 1 or score = 2), and risk ratios (RRs), risk differences, and CIs for child obesity were calculated. Results: The two standard cow's milk-based infant formulas had mean sweetness ratings of 2.58 and 3.11, followed by a cow's milk-based formula with added rice starch with a rating of 0.96, two lactose-reduced formulas with corn syrup solids with ratings of 0.87 and 2.82, and a soy-based formula with a rating of 0.83. A one-point higher sweetness rating was associated with a decreased risk of obesity at age two (RR: 0.91 [95% CI: 0.87, 0.96], p = 0.0003), age three (RR: 0.96 [95% CI: 0.93, 0.99], p = 0.02), and at age four (RR: 0.95 [95% CI: 0.92, 0.98], p = 0.002). Conclusion: The risk of obesity was decreased among WIC participants issued infant formula with a higher sweetness rating. This finding was unexpected as added sugars and lactose-reduced infant formula with corn syrup solids are associated with increase obesity risk. However, it should be noted that the standard cow’s milk-based infant formula (i.e., no added non-lactose sugars) was the WIC agency-issued formula with the highest sweetness ratings. It appears the role of sweetness and added sugars in infant formulas is complex and warrants further investigation. Future research should focus on identifying specific components of added sugars that may contribute to long-term weight outcomes. Additionally, studies should explore the metabolic and behavioral mechanisms by which non-lactose added sugars in formula might influence early childhood development.
Keywords: Sweetening agents; Taste; Dietary sugars; Formula; Infant; Infant nutrition